The variation of the angle of incidence of p waves with epicentral distance (MAUSAM, 1967)
Angles of incidence of p waves were obtained from the records of the short and long period seismographs of W.W.S.S.N. at Shillong. The study covers the range of epicentral distances from 200 to 1000. The observations indicate that the velocity of P waves at the earth’s surface is approximately 6 km/sec which is the velocity of the upper layer (granitic layer) of the earth.